Farming secondary forests in Indonesia - Jong, W. de; Noordwijk, Meine van; Sirait, M.; Liswanti, N. (2001)
Estimates of the area of swidden fallow secondary forest in Indonesia are inaccurate, partly because swidden agricultural practices giving rise to the secondary forest are heterogeneous. Throughout Indonesia, swidden agriculture is evolving into more intensive land use. A mixed secondary forest tree crop management appears to be the first stage towards a tree crop based production in Sumatra and Kalimantan. This changes the value of the forest/tree component of swidden agriculture, or the systems it evolves into. The trade offs between productivity, environmental functions, biodiversity, and sequestrated carbon are only qualitatively understood. Some of the proposed large scale estate crop production programmes in Indonesia disregard the benefits (a diverse agriculture, forest landscape, better environmental functions, higher biodiversity) that development along these endogenous trends may provide.